Robot Assisted Polyurethane Chain Extension of Dihydroxy Telechelic Depsipeptides. Issue 27 (6th June 2016) - Baudis, S.; Balk, M.; Lendlein, A.; Behl, M.
ABSTRACT: Depsipeptide-based multiblock copolymers synthesized from dihydroxy telechelic oligodepsipeptide precursors are promising candidate materials for biomedical and pharmaceutical applications. High molecular weight polymers in polyaddition reactions e.g. of diols with diisocyanates can only be reached when reactive groups are equivalent and a high conversion for this step growth polymerization is obtained. However, in depsipeptide-based multiblock urethanes reported so far, the stoichiometric ratio of the diisocyanate compound exceeded the theoretical value of 100% by far. In order to investigate the influence of the dosing system in this unusual behavior of the stoichiometric reaction two dosing devices, a solid dosing unit (SDU) and a gravimetric dosing unit (GDU) were used for a gravimetric transfer of an oligo(3- sec- butylmorpholine-2.5-dione) (OBMD) as model oligodepsipeptide. The OBMD precursor, which was transferred as a solid or as a highly viscous solution, was reacted with an isomeric mixture of 2, 2, 4- and 2, 4, 4-trimethylhexamethylene diisocyanate (TMDI) as chain extender. Two series of 49 reactions were performed and the chain extension efficacy of the building block was compared between the SDU and GDU as well as with respect to the Carothers equation. When the GDU was used the chain extension yielded higher molecular weights, proving the high accuracy of the dosing device, and the molar ratio of TMDI required for the high-throughput synthesis of the depsipeptide-based multiblock copolymers was similar to depsipeptide-based multiblock copolymers created in a classical synthesis approach.